2000
DOI: 10.1038/35017001
|View full text |Cite
|
Sign up to set email alerts
|

A regulatory link between ER-associated protein degradation and the unfolded-protein response.

Abstract: Ubiquitin conjugation during endoplasmic-reticulum-associated degradation (ERAD) depends on the activity of Ubc7. Here we show that Ubc1 acts as a further ubiquitin-conjugating enzyme in this pathway. Absence of both enzymes results in marked stabilization of an ERAD substrate and induction of the unfolded-protein response (UPR). Furthermore, basic ERAD activity is sufficient to eliminate unfolded proteins under normal conditions. However, when stress is applied, the UPR is required to increase ERAD activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
330
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 433 publications
(350 citation statements)
references
References 29 publications
16
330
1
1
Order By: Relevance
“…This agrees with the finding that treatment of human fibroblasts with SubAB during the early phase of CMV infection downregulates the expression of viral proteins even as late as 96 h after addition of the toxin (Buchkovich et al, 2008). Many reports have indicated that ERAD components are upregulated as part of UPR (Casagrande et al, 2000;Friedlander et al, 2000). However, we have not observed an upregulation of proteins involved in ERAD, such as proteasome subunits, p97/VCP or the channel forming protein derlin 1 even after 16 h of incubation with SubAB.…”
Section: Discusssionsupporting
confidence: 91%
See 3 more Smart Citations
“…This agrees with the finding that treatment of human fibroblasts with SubAB during the early phase of CMV infection downregulates the expression of viral proteins even as late as 96 h after addition of the toxin (Buchkovich et al, 2008). Many reports have indicated that ERAD components are upregulated as part of UPR (Casagrande et al, 2000;Friedlander et al, 2000). However, we have not observed an upregulation of proteins involved in ERAD, such as proteasome subunits, p97/VCP or the channel forming protein derlin 1 even after 16 h of incubation with SubAB.…”
Section: Discusssionsupporting
confidence: 91%
“…ERAD constitutively counteracts ER stress, eliminating misfolded proteins from the ER, however UPR induces its further activation through upregulation of its components (Casagrande et al, 2000;Friedlander et al, 2000). We therefore expected that treatment with SubAB would accelerate ERAD of αTCR.…”
Section: Discusssionmentioning
confidence: 98%
See 2 more Smart Citations
“…The ubiquityl ation machinery, consisting of ubiquitin activating enzyme (E1), ubiquitin conjugating enzymes (E2), and ubiquitin ligases (E3), controls substrate targeting via conjugation of ubiquitin, after which proteins are degraded by the proteasome core 41,42 . Unfolded pro teins from the endoplasmic reticulum (ER) are cleared via the ER associated degradation (ERAD) system, which induces trans location of unfolded proteins from the ER to the cytosol, from where they are cleared by the UPS 43,44 .…”
Section: The Proteostasis Network Componentsmentioning
confidence: 99%